Considering context : the role of mental workload and operator control in users' perceptions of usability - Lee, Sangwon (2013)
In developing an application, the importance of usability and user experience has become increasingly emphasized over the past few decades. An important factor in understanding these is the context in which the application is being used. To better understand the direct effect of context, two task characteristics (i.e., mental workload and operator control) were manipulated and their effects on perceived usability were examined through an experiment using simulated home security systems. The experimental results showed that both mental workload and operator control had significant effects on perceived usability. Also, the perceptions of mental workload and operator control were strongly correlated with perceived usability. The interaction between the mental workload and the operator control factors was not significant. Possible reasons for the results and practical implications for the findings are discussed.